Efektivitas Program Reward dalam Meningkatkan Loyalitas dan Disiplin Kerja Karyawan di Bank Mandiri - Putri Indriani; Ade Hani Puspa Dewi; Irdan Suwardana Yahya; Muhammad Rayhan Nurmansyah; Muhammad Khoirul Anwar (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the effectiveness of the reward program in improving employee loyalty and work discipline at Bank Mandiri. The research employs a qualitative descriptive approach using the literature study method, through the collection and analysis of secondary data obtained from official Bank Mandiri reports, academic journals, labor regulations, and media articles related to human resource management policies. The findings reveal that the implementation of both financial rewards (competitive salaries, performance-based bonuses, and welfare benefits) and non-financial rewards (recognition, promotions, and career development programs) has a positive impact on enhancing employee loyalty and work discipline. A fair, transparent, and sustainable reward system fosters a sense of belonging, strengthens affective commitment, and cultivates a productive and professional work culture. Moreover, the data indicate a decline in disciplinary violations over the past three years, demonstrating the effectiveness of the reward system as a form of positive reinforcement. This study highlights the importance of reward policies as a strategic instrument in human resource management and recommends that companies continuously adapt their reward systems to align with employee needs and the evolving work environment.